Evaluation of surface water treated with lotus plant; Nelumbo nucifera - Abd Rasid, N. S.; Naim, Mohd Nazli; Che Man, Hasfalina; Abu Bakar, Noor Fitrah; Mokhtar, Mohd Noriznan (Elsevier, 2019)
The potential of Nelumbo nucifera in treating contaminated surface water was investigated in terms of biochemical oxygen demand (BOD), chemical oxygen demand (COD), turbidity, and nitrate reduction. Batch type lab-scale container cultivated with N. nucifera was exposed to the contaminated surface water for 30 days. Nitrate (NO3−) adsorption and pH level were monitored continuously to identify the plant survival and to avoid any additional contaminants into the samples such as plant decay. For comparison, water lily, Nymphaea, was prepared using the same experimental setup. After 30 days of phytoremediation, the BOD and COD values of the treated water using N. nucifera was significantly reduced to 97.1% and 55%, respectively, due to the unique gas transport mechanism that thermodynamically drive O2 gas from leaves at the water surface to the buried rhizomes located in the anoxic sediments. When treated with Nymphaea, the BOD value in water decreased by 64.5% and the COD value increased by 50.5%. The results indicate that N. nucifera was able to remove the organic contaminants from the surface water by supplying adequate amount of 0.2–2.1 mL/min O2 gas to increase the microbial activities from the control condition.